(untitled) (Economic and Political Thought, 2015)
The aim of the article is to locate the issue of a social enterprise in the theory on how companies operate, with particular emphasis on the theory of a konfirma [a blend ‘con-firm’, coined of ‘consumer’ and ‘firm’], as well as to present a summary of the results of empirical research into social enterprises with a modified concept of the author’s theory of a konfirma. The starting point for this paper is the issue of humanization of the economic theory and empirical economic research methodology. A category of a social enterprise in the economy has been distinguished and its functions, classification and legislative attempts to regulate it have been presented. A social enterprise has been located in the theories of the firm that are discussed in contemporary literature. The theory of a konfirma is the main part of the theory of the firm identified with a social enterprise. The author has modified his theory of a konfirma for the need of including it in the category of a social enterprise. To verify the theoretical assumptions, they have been confronted with the results of empirical research into social enterprises.